Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.3382/ps.0710829
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Methionine for Stressed Laying Hens

Abstract: The effects of zinc methionine product (ZP) supplementation to Single Comb White Leghorn hens on egg production and quality were measured through three consecutive egg laying cycles. During the first and second lay cycles, ZP had minor or nonsignificant effects upon hen performance. During the third lay cycle, a low dietary Ca (.3% Ca) stress of 1 mo duration was encountered. During this low-Ca stress period, hens fed 1 g ZP/kg produced the greatest number of eggs (P less than .05), and during recovery from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 2 publications
0
7
1
4
Order By: Relevance
“…That author included 3.5% calcium in the diet supplemented with organic trace minerals and confirmed their positive effect on egg production when comparing this treatment with the diet with no organic trace mineral supplementation and 4% calcium inclusion. Kienholz (1992) found higher egg production in layers fed a diet with organic Zn supplementation and submitted to stress due to low dietary calcium level (3%), which was not observed in the present experiment.…”
Section: Effect Of Organic Selenium and Zinc On The Performance And Econtrasting
confidence: 75%
“…That author included 3.5% calcium in the diet supplemented with organic trace minerals and confirmed their positive effect on egg production when comparing this treatment with the diet with no organic trace mineral supplementation and 4% calcium inclusion. Kienholz (1992) found higher egg production in layers fed a diet with organic Zn supplementation and submitted to stress due to low dietary calcium level (3%), which was not observed in the present experiment.…”
Section: Effect Of Organic Selenium and Zinc On The Performance And Econtrasting
confidence: 75%
“…Most of the studies in the literature do not report effects of organic minerals on production, feed intake and food conversion (Kienholz, 1992;Dale & Strong, 1998;Ludeen, 2001;Sechinato, 2006), with the exception of Branton et al (1995), who observed an improvement in laying percentage of birds that received chelated minerals. Paik (2001) observed an increase in laying rate of birds 96 to 103 weeks of age that received organic copper and the association of organic Cu+Mn+Zn.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary zinc methionine enhances mononuclear phagocytic function against Salmonella arizona and Salmonella enteritidis in young turkeys [21,22]. It improves egg production and quality in hens during low calcium stress and during the recovery period [25,28].…”
Section: Zinc Methionine Complexesmentioning
confidence: 99%